Classroom Action Research as a Means of Improving Teacher Professionalism and Learning Quality in the Digital Age - Nadia Sari Putri; By Tri Agung Nusantara Kr. J. Tompong (Gateway for Understanding Research in Education, 2025)
In the digital age, challenges in education require teachers to continue to improve their professionalism and adjust learning strategies to be relevant to the needs of the 21st century. One effective approach to achieve this is through classroom Action Research (PTK).  Purpose this study aims to describe how PTK can function as a means of developing teacher professionalism and improving the quality of digital-based learning. Methods: the method used in this study is descriptive qualitative with a case study approach. The Data were collected through observation, in-depth interviews, and documentation of five teachers in Junior High School who actively implement PTK in their respective subjects. Data analysis uses Miles and Huberman interactive models, which include data reduction, data presentation, and inference. Results the results showed that the implementation of PTK encourages teachers to be more reflective of their teaching practices, adopt digital learning technologies, and be able to design interventions that have a positive impact on increasing student engagement and understanding. Significantly, teachers ' involvement in PTKS also strengthens their commitment to self-development and professional collaboration. Implications: PTK is not only a tool to improve classroom learning, but also a lifelong learning strategy for teachers in the digital age. Conclusion: in conclusion, PTK proved to be a relevant and effective means in improving teacher professionalism while improving the quality of learning systematically and contextually.